Effect of water-sediment regulation operation on sediment grain size and nutrient content in the lower Yellow River. (10th January 2021) - Hou, Chuanying; Yi, Yujun; Song, Jie; Zhou, Yang
Abstract: The Yellow River (YR) is famous for its high sediment concentration. The Xiaolangdi dam (XLD), the most downstream dam on the mainstream of the YR, plays an integral role in siltation mitigation, flood defence, agriculture, and hydropower generation. To alleviate siltation of the Xiaolangdi Reservoir (XLDR) and riverbed uplift of the lower reaches of the YR and strengthen flood control safety downstream, the XLDR began to implement water-sediment regulation in 2002. Water-sediment regulation (WSR) has significantly changed the hydrological processes, erosion and deposition, and sediment transport in the downstream channel, and the downstream water environmental conditions have also changed. In this study, 10 sections in the Lower Yellow River (LYR, from the XLDR to the Lijin section) and 4 sections in the soft floodplain area were sampled in the field to analyse their surface sediment grain size composition and nutrient content. At the same time, data on the average annual median particle sizes (D50 ) of channel sediments and suspended particles in 7 typical sections in the LYR from 2004 to 2015 were statistically analysed. The results show that the channel sediment grain size in the LYR decreased along the river course, and the D50 ranged from 0.20 mm in the HYK section to 0.08 mm in the LJ section. Moreover the D50 of the suspended sediment was less than 0.05 mm. The D50 of the channel and suspended sediment were both ranked as follows: non-flood season > flood season > WSR period. After WSR, fine silt particles with diameters of 0.01–0.05 mm were deposited on the soft floodplain. The channel sediment size was mainly coarse particles with diameters of 0.05–0.20 mm due to channel erosion. The suspension of fine silt particles due to flood scouring led to the total organic carbon (TOC) and total nitrogen (TN) absorbed in the particles to also be resuspended in the water. As a result, the TOC and TN contents in the channel sediments decreased by approximately 40% after WSR. Highlights: The sediment grain size in the Lower Yellow River decreased along the river course. The average median particle size of the channel and the suspended sediment in the Lower Yellow River over many years was in the following order: non-flood season > flood season > water-sediment regulation period. The channel was scoured, and the beach area underwent deposition because of water-sediment regulation. The regulation is conducive to the sediment transport in downstream during flooding season. The Xiaolangdi water-sediment regulation resulted in a decrease of approximately 40% in the TOC and TN contents in the sediments in the Lower Yellow River.